1992
DOI: 10.1093/clinchem/38.7.1379
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Occurrence of Macro Creatine Kinase in One Family

Abstract: We measured creatine kinase (CK, EC 2.7.3.2), CK-MB isoenzyme activity and mass concentration, and distribution of CK isoenzymes (by electrophoresis) in serum from five members of one family. The mother and two young children showed CK-IgG complexes in their sera. The concentration of the CK-IgG complexes in the children decreased over time, suggesting that the complex involved maternal IgG and had been transferred across the placenta from the mother to her children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Bayer et al reported an infantile case of macro CK caused by maternal Ig. 9 Consistent with our results, they reported that CK activity had normalized by 6 months of age but that the macro CK activity band remained visible by electrophoresis after CK levels had normalized, and finally disappeared at 26 months of age. 9 In general, passively acquired Ig are cleared by 10-12 months after birth.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Bayer et al reported an infantile case of macro CK caused by maternal Ig. 9 Consistent with our results, they reported that CK activity had normalized by 6 months of age but that the macro CK activity band remained visible by electrophoresis after CK levels had normalized, and finally disappeared at 26 months of age. 9 In general, passively acquired Ig are cleared by 10-12 months after birth.…”
Section: Discussionsupporting
confidence: 92%
“…9 Consistent with our results, they reported that CK activity had normalized by 6 months of age but that the macro CK activity band remained visible by electrophoresis after CK levels had normalized, and finally disappeared at 26 months of age. 9 In general, passively acquired Ig are cleared by 10-12 months after birth. But our investigation and the report by Bayer et al 9 suggest that maternal Ig can bind to enzymes strongly and that some Ig may remain in the infant's circulation for more than one year.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An important cause for false, persistently elevated levels of CK and/or CK -MB is the apparition of macroCK. If normal CK is a globular dimeric protein with molecular weight of 43 kDa, macroCK is an octameric protein that is a complex formed by CK -MM and CK -MB with a immunoglobulin (Ig) usually Ig G with a kappa light chain, but sometimes Ig A or Ig M -type I of macroCK (molecular weight >200 kDa) or a polymer of mitochondrial CK -type II of macroCK (molecular weight >300 kDa) [3,4,9,[26][27][28]. The electrophoretic separation using agarose gel is useful for detecting normal CK and macroCK and immunofixation with antisera against Ig G is used for type I macroCK [3,22,[26][27][28][29][30].…”
mentioning
confidence: 99%
“…If normal CK is a globular dimeric protein with molecular weight of 43 kDa, macroCK is an octameric protein that is a complex formed by CK -MM and CK -MB with a immunoglobulin (Ig) usually Ig G with a kappa light chain, but sometimes Ig A or Ig M -type I of macroCK (molecular weight >200 kDa) or a polymer of mitochondrial CK -type II of macroCK (molecular weight >300 kDa) [3,4,9,[26][27][28]. The electrophoretic separation using agarose gel is useful for detecting normal CK and macroCK and immunofixation with antisera against Ig G is used for type I macroCK [3,22,[26][27][28][29][30]. Type I of macroCK is migrating between CK -MM and CK -MB (anodal type of macroCK) and type II of macroCK is migrating cathodic to CK -MM (cathodal type of macroCK) [4,22,[26][27][28][29][30].…”
mentioning
confidence: 99%